Effect of sowing date and plant spacing on seed production of cauliflower (Bangladesh Journal of Agricultural Research, 2015)
The experiment was conducted at Regional Agricultural Research Station, Ishurdi, Pabna during rabi season of 2011-2012 and 2012-2013 to find out the appropriate sowing date and optimum plant spacing for seed production of cauliflower (var. BARI Phulcopi-1). Four sowing dates viz. 20 September, 1 October, 10 October and 20 October and three plant spacing viz. 60 cm × 50 cm, 60 cm × 60 cm and 60 cm × 70 cm were used as treatment variables. Significant variation in seed yield and yield contributing characters of cauliflower were observed due to execution of different sowing dates and plant spacing. Number of branches plant-1, number of pods plant-1 and number of seeds pod-1 showed the highest in 1 October sowing as a result the highest seed yield (361.69 kgha-1) was obtained from same date of sowing. Sowing on 10 October and 20 October reduced seed yield drastically compared to that obtained from 1 October sowing. The lowest seed yield (188.54 kgha-1) was obtained from 20 October sowing. On the contrary, closer spacing (60 cm × 50 cm) produced the highest seed yield (315.88 kgha-1) and the wider spacing (60 cm × 70 cm) produced the lowest seed yield (254.07 kgha-1). However, combination of 1 October sowing with 60 cm × 50 cm plant spacing produced the highest seed yield (414.81 kgha-1) due to higher number of seeds pod-1. The seed yield decreased after 10 October sowing irrespective of plant spacing. So, early sowing (1 October) with closer spacing (60 cm× 50 cm) would be economically profitable for cauliflower seed production in North-Western part of Bangladesh.Bangladesh J. Agril. Res. 40(3): 491-500, September 2015